Evaluasi Penerapan Ambang Batas Parlemen (Parliamentary Threshold) Dalam Penyederhanaan Partai Politik - Afif, Muhammad (Lareh Law Review, 2025)
This research reviews the evaluation of the application of parliamentary thresholds in simplifying political parties in Indonesia with a focus on the dynamics of general elections and the consequences of implementing parliamentary thresholds on political party structures. By analyzing changes in threshold values ​​from the 2009 Election to the 2024 Election, this research highlights the normative evolution and practical impact. Apart from that, this research also explores the impact of thresholds on the simplification of political parties, especially in the context of cadre formation. Using a juridical-normative research methodology approach, this research details the development of parliamentary thresholds in Indonesia and discusses the Constitutional Court's decision which indicates the need for further evaluation. So far, the application of thresholds has not had a significant effect in simplifying political parties and has not been able to become a means of encouraging political parties to carry out better cadre formation. It is hoped that a critical evaluation of the parliamentary threshold system can provide a constructive contribution to improving and improving the general election system in the future. Keywords: Evaluation, Parliamentary Threshold, Political Party